Revitalisasi Nilai Islam dalam Adat Perkawinan pada Tradisi Piti Rambang - Yuniardi, Harry (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze the practice of Piti Rambang in the perspective of Islamic civil law, as well as how the revitalization of Islamic values can be applied to harmonize customs with the principles of justice and protection of women's rights. This study uses an analytical descriptive method with a normative-empirical approach. The normative approach is carried out through the study of Islamic law, the Marriage Law, and human rights law in Indonesia. Meanwhile, an empirical approach is carried out through secondary data analysis related to Piti Rambang's practices, interviews with traditional leaders, academics, and women activists in Sumba. The results of the study show that the practice of Piti Rambang is contrary to the basic principles of marriage in Islam, which emphasizes the willingness of both parties (ridha) and gender justice. In national law, this practice violates the provisions of Article 6 of Law Number 1 of 1974 concerning Marriage, which requires the consent of both prospective brides. In addition, Piti Rambang can also be categorized as a violation of human rights and kidnapping based on Articles 328 and 333 of the Criminal Code. As an effort to revitalize Islamic values in marriage customs, it is necessary to carry out a reconstruction of customary law that is more oriented towards the values of sakinah, mawaddah, wa rahmah, as well as education to the public about women's rights in marriage. Local governments, religious leaders, and women's protection institutions must play an active role in conducting socialization and advocacy to ensure that Islamic customs and laws can run in harmony without harming certain parties, especially women.